[PP.03.22] REFLECTED WAVES ARE RELATED TO AORTA LENGTH MEASURED BY MRI IN ELDERLY. (September 2017) - Joly, L.; Salvi, P.; Labat, C.; Mandry, D.; Micard, E.; Beaumont, M.; Marie, P.Y.; Benetos, A.
Abstract : Objective: Central pressure waveform can be decomposed into pressure transmission and reflection waves. Aorta impedance (Zc) can be measured through recording pulse pressure signal and aortic flow signal. Zc reflects structural and functional properties of elastic central and peripheral muscular arteries. Design and method: This study proposed a novel method using wave intensity analysis to assess reflected waves by decomposition of magnetic resonance imaging (MRI) of central aortic flow and central aortic pressure waveforms measured by tonometry in 30 older subjects allowing to obtain Zc in time domain, reflection index (IR) and reflection magnitude (MR). Therefore a graphical user interfaces and methods for automatic signal treatments were programmed. Results: Elderly patients were mean aged of 75.25 ± 5.85 years (14 female, 16 male). No significant differences were observed between gender groups in terms of weight, height, pressure parameters and impedances parameters. Mean Zc value was 424.34 ± 94.41 DSC for the whole aging population. We found a strong negative association between Zc and LVET (r = −0.53, p = 0.004) and a trend of negative association between Zc and aortic diameter, at the aortic root, (r = −0.36, p = 0.05). RM associated positively with thoracic aorta length (r2 = 0.15, p = 0.04) after adjustment to age and height, IR also associated positively with thoracic aorta length (r2 = 0.16, p = 0.04) after adjustment to age and height. Conclusions: This automatical signal treatment of aortic flow and pulse pressure waveform is a good MRI method for assessment of wave reflections in older subjects allowing obtaining reflection magnitude. What can be observed is that reflected waves depended strongly on thoracic aorta length. Moreover, Zc is inversely correlated to left ventricular ejection time and aortic diameter.